Civic virtues dalam pendidikan moral dan kewarganegaraan di Indonesia era orde baru - Samsuri Samsuri (Universitas Negeri Yogyakarta, 2004)
This paper described the role of New Order Regime in Indonesia to build the citizen characters through the educational system. The regime effort to inculcate its interpretation on Pancasila (Five Principles) such as